White sight : visual politics and practices of Whiteness / Nicholas Mirzoeff. - Mirzoeff, Nicholas, 1962- (The MIT Press, 2023)
Analysing recent events like the George Floyd protests and the Central Park birdwatching incident, Nicholas Mirzoeff suggests that we are experiencing a general crisis of White supremacy that presents both opportunities and threats to social justice. If we do not seize this moment to dismantle White sight, then White supremacy might surge back stronger than ever. To that end, he highlights activist interventions to strike the power of the White heteropatriarchal gaze. 'White Sight' is a vital handbook and call to action for anyone who refuses to live under White-dominated systems and is determined to find a just way to see the world.